2018
DOI: 10.5194/hess-22-3825-2018
|View full text |Cite
|
Sign up to set email alerts
|

Estimating epikarst water storage by time-lapse surface-to-depth gravity measurements

Abstract: The magnitude of epikarstic water storage variation is evaluated in various karst settings using a relative spring gravimeter. Gravity measurements are performed over a 1.5-year period at the surface and inside caves at different depths on three karst hydro-systems in southern France: two limestone karst systems and one dolomite karst system. We find that significant water storage variations occur in the first 10 m of karst unsaturated zone. The subsurface water storage is also evidenced by complementary magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…I wonder also whether flow measurements of springs or a river are available which could be a proxy for the underground storage system, also if tens of km distant from the gravity campaign site. The geodetic observations of gravity (Champollion et al, 2018;Van Camp et al 2006) and of tilt (Grillo et al 2018, Tenze et al 2012, Devoti et al 2015 in different karstic areas showed good correlation to rainfall, springs and river, as these last drain the karstic storage and thus are a proxy for the hydrologic mass variations. Since the hydrologic mass variation is crucial in the estimate of the anticipated subsoil erosion, this point could be investigated further in the manuscript.…”
mentioning
confidence: 94%
“…I wonder also whether flow measurements of springs or a river are available which could be a proxy for the underground storage system, also if tens of km distant from the gravity campaign site. The geodetic observations of gravity (Champollion et al, 2018;Van Camp et al 2006) and of tilt (Grillo et al 2018, Tenze et al 2012, Devoti et al 2015 in different karstic areas showed good correlation to rainfall, springs and river, as these last drain the karstic storage and thus are a proxy for the hydrologic mass variations. Since the hydrologic mass variation is crucial in the estimate of the anticipated subsoil erosion, this point could be investigated further in the manuscript.…”
mentioning
confidence: 94%
“…These techniques have also been successfully applied in karst environments (e.g. Jacob et al, 2009;Fores et al, 2014;Champollion et al, 2018;Mouyen et al, 2019;Watlet et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Water in the shallow subsurface is subject to evapotranspiration. If there is soil, it can play an important role in infiltration velocity and mixing processes (Charlier et al, 2012;Perrin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the antecedent moisture conditions influence the storage capacity of water and infiltration rate. Under dry conditions, a larger portion of water can be stored, but subsurface flows are less important than under wet antecedent conditions (Charlier et al, 2012;Fu et al, 2015;Trček, 2007). Finally, vegetation and climate influence karst recharge processes.…”
Section: Introductionmentioning
confidence: 99%